Clinical Case of Immune Dysregulation, Polyendocrinopaty, Enteropathy, X-Linked (IPEX) Syndrome with Severe Immune Deficiency and Late Onset of Endocrinopathy and Enteropathy - R. Savova; M. Arshinkova; J. Houghton; M. Konstantinova; M. Gaydarova; E. Georgieva; G. Popova; V. Genova; N. Tomova; A. Anadoliiska; K. Koprivarova (Case Reports in Medicine)
Objective. To describe the clinical characteristics of IPEX syndrome in a child with FOXP3 mutation. Clinical Case. A boy aged 2.3 years was born from first normal pregnancy with a weight of 3420 gr. Family History. Two brothers of the mother died before the age of 3 years with severe infections, diarrhea, erythroderma, and elevated immunoglobulins class E (IgEs). Since first month of life, our patient suffered from septicemia, pneumonias, pyelonephritis, and meningitis, accompanied with eczematous dermatitis and IgEs up to 4000 IU/L (normal <10). At the age of 1.6 years, he developed type 1 diabetes mellitus (T1DM). He was underweighted (−3.42 SDS) and had some phenotypic features like coarse face, muscle hypotonia, joint hyperextensibility, eczematous dermatitis, and subcutaneous cold abscesses. Autoimmune thyroiditis and celiac disease were excluded. After diabetes, intermittent watery diarrhea appeared with progression to severe intractable form. Finally, aggravating symptoms of nephritis, cachexia, and respiratory insufficiency were the cause for his death at the age of 2 years and 3 months. The DNA analysis at the University of Exeter Medical School established mutation at exon 10 of FOXP3 gene c.1010G >A, p. (Arg337Gln), which confirmed IPEX syndrome. The same mutation in heterozygotic state was found in the mother. A prenatal diagnosis of her second pregnancy ensured a daughter carrier of the mutation.